EXTH-27. INFLAMMATORY REPROGRAMMING OF GLIOMAS USING DELTA-24-RGDOX AND IMMUNOMETABOLIC ADJUVANTS. (5th November 2018) - Nguyen, Teresa; Rivera-Molina, Yisel; Puerta Martinez, Francisco; Fan, Xuejun; Henry, Verlene; Jiang, Hong; Lang, Frederick; Fueyo, Juan; Gomez-Manzano, Candelaria
Abstract: The immunosupressive microenvironment of glioblastoma (GB) is responsible for the resistance to therapies and its dismal prognosis. Several lines of evidence have linked brain tumor metabolism and immunoresistance with the presence of active metabolic pathways. In this regard, activation of indolamine-2, 3-dioxygenase (IDO) in regulatory T-cells favors tumor immunosuppression. We have observed that the implantation of tumors in mice generates an immunosuppressive environment characterized by overrepresentation of CD4+ regulatory T-cells and MDSCs. Treatment with the oncolytic adenovirus, Delta-24-RGD, has been shown to induce complete responses in a subset of GB patients by reprogramming the immune response. Moreover, the anti-tumor cytotoxic properties of T-cells can be enhanced by the addition of immune agonists, such as OX40L, a T-cell activator. We hypothesized that the combination of IDO inhibition (1MT or Indoximod) and Delta-24-RGD armed with the OX40 ligand (Delta-24-RGDOX) synergizes and have a therapeutic effect in GB. In this study, orthotopic GB were implanted in immunocompetent mouse and treated with the combination of D24-RGDOX and 1MT. Delta-24-RGDOX treatment resulted in a significant survival benefit compared to the control groups (mean survival, 46.5 vs. 38.5 days, P =0.02). Interestingly, the combination treatment of Delta-24-RGDOX and the IDO inhibitor induces complete tumor regression and the production of a higher percentage of long-term survivors compared to single therapy with Delta-24-RGDOX (mean survival, 46.5 vs. 108.5 days, P =0.03). Moreover, when the long-term glioma survivors were re-challenged with similar glioma cells, we observed 100% survival ( P =0.002), indicating the establishment of immune memory by the combination therapy. Furthermore, functional studies showed a significant increase in anti-tumor activity of splenocytes from GB bearing treated mice that were treated with the combined therapy D24-RGDOX and Indoximod ( P =0.009). These data support the use of immunometabolic adjuvants in combination with virotherapy as a potential treatment of patients with GB.